(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ci-ca is a French word which means back-and-forth motion. The patent and public health are two sides of the ci-ca (titter totter). If one is focused another one has to be compromised. But suppression of anyone will result into less efficient medicines or may create costly life drugs. Consequently it will result into less efficient market as well as human resources. The policy maker should think to balance the two sides which sometimes seem opposite to each other because innovation, market and public health everything is important for a developing country.